A distributed virtual hypercube algorithm for maintaining scalable and dynamic network overlays. (25th July 2014) - Bona, L. C. E.; Duarte, E. P.; Fonseca, K. V. O.
Summary Network overlays support the execution of distributed applications, hiding lower level protocols and the physical topology. This work presents DiVHA: a distributed virtual hypercube algorithm that allows the construction and maintenance of a self‐healing overlay network based on a virtual hypercube. DiVHA keeps logarithmic properties even when the number of nodes is not a power of two, presenting a scalable alternative to connect distributed resources. DiVHA assumes a dynamic fault situation, in which nodes fail and recover continuously, leaving and joining the system. The algorithm is formally specified, and the latency for detecting changes and the subsequent reconstruction of the topology is proved to be bounded. An actual overlay network based on DiVHA called HyperBone was implemented and deployed in the PlanetLab. HyperBone offers services such as monitoring and routing, allowing the execution Grid applications across the Internet. HyperBone also includes a procedure for detecting groups of stable nodes, which allowed the execution of parallel applications on a virtual hypercube built on top of PlanetLab. Copyright © 2014 John Wiley & Sons, Ltd.